Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pekerja Sektor Informal: Kajian Literatur - Dewi Mulyawati, Sita; Arham Widarso, Mahajendra (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Indonesia's industrial sector is growing rapidly, and the informal sector plays a significant role in regional economic development. However, many workplace accidents in Indonesia's informal sector remain unrecorded and unrecognized. This study aims to identify the main factors influencing the use of personal protective equipment (PPE). The study uses a literature review method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) strategy to select valid and relevant sources clearly and consistently. The search strategy uses Google Scholar and Garuda within the timeframe of 2022–2025. The literature search and selection process was conducted over a two-month period, from March to April 2025. Of the 530 articles found in the article search, five were deemed relevant and met the criteria for analysis in this study after screening. Compliance with PPE use in the informal sector is significantly influenced by knowledge and attitude as well as the availability of PPE and workplace and psychosocial factors. Adequate knowledge and positive attitudes are the main foundations for establishing safe work behavior. However, compliance with PPE use in the informal sector still faces various complex challenges. The main influencing factors are the level of knowledge and attitudes of workers, the availability of PPE, and support for occupational health and safety (OHS) socialization. Therefore, improving compliance with PPE use requires education, training, adequate PPE provision, strict supervision, and OHS socialization tailored to the informal sector's characteristics.